Clinical characteristics of colonization of the amniotic cavity in women with preterm prelabor rupture of membranes, a retrospective study - Kacerovsky, Marian; Stranik, Jaroslav; Matulova, Jana; Chalupska, Martina; Mls, Jan; Faist, Tomáš; Hornychova, Helena; Kukla, Rudolf; Bolehovska, Radka; Bostik, Pavel; Jacobsson, Bo; Musilova, Ivana (Scientific reports, 2022)
To determine the main clinical characteristics of preterm prelabor rupture of membranes (PPROM) complicated by colonization of the amniotic cavity (microbial invasion of the amniotic cavity without intra-amniotic inflammation). A total of 302 women with PPROM were included. Transabdominal amniocentesis was performed and amniotic fluid was assessed. Based of microbial invasion of the amniotic cavity and intra-amniotic inflammation (interleukin-6 ≥ 3000 pg/mL), the women were divided into following groups: intra-amniotic infection, sterile intra-amniotic inflammation, colonization of the amniotic cavity, and negative amniotic fluid. Colonization was found in 11% (32/302) of the women. The most common bacteria identified in the amniotic fluid were Ureaplasma spp. with a lower burden than those with intra-amniotic infection (p = 0.03). The intensity of intra-amniotic inflammatory response measured by interleukin-6 was higher in women with colonization than in those with negative amniotic fluid (medians: 961 pg/mL vs. 616 pg/mL; p = 0.04). Women with colonization had higher rates of acute inflammatory placental lesions than those with negative amniotic fluid. In PPROM, colonization, caused mainly by microorganisms from the lower genital tract, might represent an early stage of microbial invasion of the amniotic cavity with a weak intra-amniotic inflammatory response.
Keywords: předčasný odtok plodové vody; plodová voda; retrospektivní studie; Inflammation; Chorioamnionitis; Pregnancy; těhotenství; Interleukin-6; Placenta; zánět; Fetal Membranes, Premature Rupture; novorozenec; placenta; Amniotic Fluid; lidé; chorioamnionitida; ženské pohlaví; interleukin-6; Humans; Infant, Newborn; Retrospective Studies; Female